Embolic focus - Mazza Bruno, Milton E (Cirugía del Uruguay, 1971)
The thrombotic focus is studied with respect to its primitive site, followed by an analysis of superficial and deep venous thrombosis and of the relation between pulmonary thrombosis and embolism. An aspect which is worthy of note is the frequency of silent emboligenous thrombosis; forms are not the most emboligenous